The Influence of Content Marketing, Brand Awareness, E-WOM and Product Knowledge Towards Purchase Intention (A Case Study on Oatside Customers in Medan) - Rahardjo, Jeanette Audrey; Jeybi, Jeybi; Wijaya, Jesslyn; Putri, Siti Alyaa; Alfonsius, Alfonsius (Proceeding of International Conference on Entrepreneurship (IConEnt), 2023)
Oatside is a Singapore-owned company established in 2021 which offers variants of plant-based milk made of oats. It started being sold in Indonesia in early 2022, and it has gained popularity since then. The objective of the research is to identify the influence of content marketing, brand awareness, product knowledge and E-WOM towards the purchase intention of Oatside customers in Medan. In this paper, we will be using the quantitative research method to collect data which is implemented through questionnaires survey with likert scale. And for the analysis technique, we use the SEM or known as Structural Equation Modeling to process the data with Analysis of Moment Structure (AMOS) 22 Software. This research is conducted to see whether the influence of content marketing, brand awareness, E-WOM and product knowledge towards purchase intention on Oatside customers in Medan. The research shows that there is a significant influence in product knowledge on the purchase intention while other variables have no significant impact on the purchase intention.